2015
DOI: 10.1021/jp510427v
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of the Rutile TiO2(110) Surface Enhancing Its Reducing Power for Photocatalysis

Abstract: Hydroxylation of the rutile TiO2(110) surface has attracted much attention as the excess unpaired electrons introduced by hydroxyls play a critical role in surface chemistry and photocatalysis process of this material. In this work, based on density functional theory calculations with the Hubbard U correction, the electronic structures of the hydroxylated TiO2(110) surfaces have been studied. One interesting effect is found that the hydroxylation can elevate band edges of TiO2, and thus can enhance its reducin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 52 publications
4
63
0
Order By: Relevance
“…For example, it is known that OH groups donate electrons to the oxide lattice in much the same way as V O s [595], and that this affects the binding strength of coadsorbed atoms and molecules, and can have a direct impact on surface chemistry [596]. Moreover, it has been shown that the nucleation of Au clusters occurs homogeneously on the terraces on a TiO 2 (110) surface with V O s, but preferentially occurs at step edges in the presence of OH [597].…”
mentioning
confidence: 99%
“…For example, it is known that OH groups donate electrons to the oxide lattice in much the same way as V O s [595], and that this affects the binding strength of coadsorbed atoms and molecules, and can have a direct impact on surface chemistry [596]. Moreover, it has been shown that the nucleation of Au clusters occurs homogeneously on the terraces on a TiO 2 (110) surface with V O s, but preferentially occurs at step edges in the presence of OH [597].…”
mentioning
confidence: 99%
“…According to our previous study, 26 such embedded polarons are only weakly contribute to the total dipole moment comparing with the exposed hydroxyl, as well as the exposed O-vac here.…”
mentioning
confidence: 55%
“…26 The stoichiometric rutile TiO2 (110) surface 11 itself is non-polar and has a neglectable dipole moment of only~0.15 Debye given by our DFT+U calculation. However, when the surface is reduced, the dipoles are created.…”
Section: +mentioning
confidence: 88%
“…The optimized lattice constant of rutile TiO 2 is in good agreement with experimental ones, where the differences between DFT result and experimental values are only 0.043% for the a/b‐axes and 0.23% for the c‐axis. Unlike the prefect TiO 2 (110) surface (Figure A), the density of states (DOS) with oxygen vacancy (Figure B) shows two excess electrons donated by the two specific Ti atoms, implying that the adjacent Ti atoms changed from Ti 4+ to Ti 3+ . According to the ligand field for octahedral coordinated metal oxide, the excess electron would occupy one of Ti's 3d t 2g orbitals, which can lead to the local Jahn‐Teller distortion due to the electron‐lattice coupling .…”
Section: Resultsmentioning
confidence: 99%
“…To further explore this interpretation, we performed calculations based on density functional theory (DFT) . Four kinds of models are built as following: (1) the perfect TiO 2 (110) interface (TiO 2 , Figure A top image); (2) the TiO 2 (110) interface with oxygen vacancy (TiO 2 ‐O 2c , Figure A bottom image); (3) single PbS molecule adsorbed on the TiO 2 (110) interface with O 2c site (PbS@TiO 2 ‐O 2c , Figure B); (4) single CdS molecule adsorbed on the O 2c site of the TiO 2 (110) interface (CdS@TiO 2 ‐O 2c , Figure C).…”
Section: Resultsmentioning
confidence: 99%